Batik Buketan Motif Bunga Nasional Indonesia Dan Penerapannya Dalam Busana Bernuansa Vintage - Budiarti Nafisah; Esther Mayliana; I Made Sukanadi (Style : Journal of Fashion Design, 2021)
National flowers are considered to represent the character of the nation and state. The flowers chosen as the national flower of Indonesia are white jasmine, moon orchid, and raflesia arnoldi. Floral motifs have often been used as a source of ideas for making batik since ancient times, one of which is the Bouquetan batik motif which was popularized by Dutch women at that time. classic style.The author makes four collections of works entitled "TOENEMEN", meaning that it grows as the idea taken in this work is the Indonesian national flower, these three flowers have a deep philosophy about the value of a nation or individual, the values needed for growth are sincerity, kindness, beauty. also unique.